2019
DOI: 10.1186/s12917-019-1954-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hypoxia on chondrogenesis of equine synovial membrane-derived and bone marrow-derived mesenchymal stem cells

Abstract: Background Joint injury is extremely common in equine athletes and post-traumatic osteoarthritis (PTOA), a progressive and debilitating disease, is estimated to affect 60% of horses in the USA. The limited potential for intrinsic healing of articular cartilage has prompted intense efforts to identify a cell-based repair strategy to prevent progression of PTOA. Mesenchymal stem cells (MSCs) have the potential to become an ideal source for cell-based treatment of cartilage lesions; however, full cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
4
9
0
Order By: Relevance
“…Type II collagen expression is positively related with chondrogenic capacity (Gale et al, 2019) and was previously shown to significantly decrease under hypoxic conditions (Anderson et al, 2016). Similarly, we found that hypoxia significantly decreased the expression of type II collagen (Col2) protein in mandibular chondrocytes compared to that in controls and cells treated with LIPUS (Figures 2A, B).…”
Section: Lipus Treatment Increases Type II Collagen Expression and Prsupporting
confidence: 75%
“…Type II collagen expression is positively related with chondrogenic capacity (Gale et al, 2019) and was previously shown to significantly decrease under hypoxic conditions (Anderson et al, 2016). Similarly, we found that hypoxia significantly decreased the expression of type II collagen (Col2) protein in mandibular chondrocytes compared to that in controls and cells treated with LIPUS (Figures 2A, B).…”
Section: Lipus Treatment Increases Type II Collagen Expression and Prsupporting
confidence: 75%
“…Gale et al analyzed the chondrogenic differentiation potential of equine synovial membrane and bone marrow derived MSCs and found no appreciable difference between cells cultured either at 5% oxygen or in normoxic conditions for 28 days. The results of expression of chondrogenic genes SOX9, ACAN, and COL2b were also variable between the groups [79]. Similar to this Li J and Pei M found no significant differences in chondrogenic index between normoxic and 5% hypoxic culturing for 7 days in synovium derived MSCs [80].…”
Section: Hypoxia Improves Differentiation Potential Of Cellssupporting
confidence: 76%
“…In a review of MSCs derived from other species, all species noted some difficulties exhibiting expression of the 3 classic MSC markers. In the equine literature, CD73 and CD105 are most often unreported or negative (de Mattos Carvalho et al, 2009 ; Radcliffe et al, 2010 ; Ranera et al, 2011 ; Maia et al, 2013 ; Barberini et al, 2014 ; Alipour et al, 2015 ; Zahedi et al, 2017 ; Gale et al, 2019 ; Kamm et al, 2019 ; Lepage et al, 2019 ). In mouse literature, there are several examples of researchers being able to demonstrate one marker and not the other two, but no clear pattern as to which marker is shown to have positive expression (Meirelles Lda and Nardi, 2003 ; Anderson et al, 2013 ; Hosseinzadeh Shirzeily et al, 2013 ; Deng et al, 2014 ; Li and Niyibizi, 2016 ; Ahmed et al, 2017 ).…”
Section: Challenges For Clinical Translation Of Mesenchymal Stromal Cmentioning
confidence: 99%
“…CD29, integrin beta-1, is a cell surface receptor that is involved in cell adhesion. CD29 has been found to be “highly” expressed (≥95%) on MSCs derived from human (Hu et al, 2003 ; Le Blanc et al, 2003 ; Wexler et al, 2003 ; Brooke et al, 2008 ; Pruszak et al, 2009 ; Park and Patel, 2010 ; Aldridge et al, 2012 ; Al-Nbaheen et al, 2013 ; Guan et al, 2014 ; Yang et al, 2014 ; Alrefaei et al, 2015 ; Katsiani et al, 2016 ; Van Pham et al, 2016 ; Togarrati et al, 2018 ; Kaviani et al, 2019 ), rat (Wu et al, 2009 ; Walker et al, 2010 ; Song et al, 2014 ; Davies et al, 2015 ; Suto et al, 2017 ), equine (Ranera et al, 2011 ; Alipour et al, 2015 ; Esteves et al, 2017 ; Zahedi et al, 2017 ; Gale et al, 2019 ; Lepage et al, 2019 ), canine (Filioli Uranio et al, 2011 ; Choi et al, 2013 ; Ivanovska et al, 2017 ), mouse (Meirelles Lda and Nardi, 2003 ; Ahmed et al, 2017 ), porcine (Ock et al, 2010 ; Lee et al, 2015 ; Wiater et al, 2018 ), buffalo (Deng et al, 2018 ), rabbit (Lee et al, 2013 ; Kovac et al, 2017 ), bovine (Corradetti et al, 2013 ; de Moraes et al, 2016 ), and chickens (Bai et al, 2013 ). Evidence suggests that CD29 expression may be involved with MSC migration along with CD73 (Ode et al, 2011 ).…”
Section: Challenges For Clinical Translation Of Mesenchymal Stromal Cmentioning
confidence: 99%